Dilated cardiomyopathy and chronic cardiac inflammation: Pathogenesis, diagnosis and therapy. (27th August 2022) - Harding, Daniel; Chong, Ming H. A.; Lahoti, Nishant; Bigogno, Carola M.; Prema, Roshni; Mohiddin, Saidi A.; Marelli‐Berg, Federica
Abstract: Dilated cardiomyopathy (DCM) is typically defined by left ventricular dilation and systolic dysfunction in the absence of a clear precipitant. Idiopathic disease is common; up to 50% of patients with DCM have no cause found despite imaging, genetic and biopsy assessments. Treatment remains focused on managing symptoms, reducing the risk of sudden cardiac death and ameliorating the structural and electrical complications of disease progression. In the absence of aetiology‐specific treatments, the condition remains associated with a poor prognosis; mortality is approximately 40% at 10 years. The role of immune‐mediated inflammatory injury in the development and progression of DCM was first proposed over 30 years ago. Despite the subsequent failures of three large clinical trials of immunosuppressive treatment (ATTACH, RENEWAL and the Myocarditis Treatment Trial), evidence for an abnormal adaptive immune response in DCM remains significant. In this review, we summarise and discuss available evidence supporting immune dysfunction in DCM, with a specific focus on cellular immunity. We also highlight current clinical and experimental treatments. We propose that the success of future immunosuppressive treatment trials in DCM will be dependent on the deep immunophenotyping of patients, to identify those with active inflammation and/or an abnormal immune response who are most likely to respond to therapy. Abstract :